Strategies and Difficulties of Madrasah Teachers in Teaching English Vocabulary for Young Learners - Riris Sugianto; Lalu Jaswadi Putera (Lembaga Yasin AlSys, 2025)
Vocabulary instruction is a critical component of early English language education, significantly contributing to the long-term language development of young learners. However, effectively selecting and applying teaching strategies that align with students’ cognitive and affective needs poses notable challenges, particularly for teachers in madrasah ibtidaiyah (Islamic primary schools). These challenges are often compounded by factors such as limited parental involvement, overcrowded classrooms, scarce teaching resources, and constrained instructional time. This study investigates the vocabulary teaching strategies employed by English for Young Learners (EYL) madrasah teachers and the difficulties they encounter in their implementation. Using a qualitative descriptive design, data were gathered through classroom observations and semi-structured interviews with groups of madrasah teachers. The findings reveal that strategies such as “listen and repeat” and “question and answer” were widely adopted, while approaches like “demonstration,” “brainstorming,” “translation,” and “outdoor activities” were used selectively based on students’ grade levels. Teachers consistently reported various obstacles, including low student motivation, diverse proficiency levels, limited instructional materials, and insufficient time allocated for English instruction. These insights highlight the need for context-responsive pedagogical support and resource development to enhance vocabulary learning outcomes in Islamic primary school settings.